Composition of Essential Oil of Healthy and Diseased Indian Rosewood Trees (Dalbargia Sissoo DC.) (Bangladesh Journal of Botany, 2022)
The evergreen rosewood tree (Dalbargia sissoo or Indian rose wood tree), was once a major source of fuel wood and later used in the furniture industry, is now dying in a slow and mysterious death across Pakistan, India and other South Asian countries. In the present study chemical changes produced in essential oil of diseased Dalbergia sisso and chemical derivatization of essential oil were investigated to determine antioxidant and antitermitic activities. The potential ability of secondary metabolites present in disease affected trees was much lower to act as effective antioxidants to fight against oxidative damage. Results obtained showed that Tetradecane, Tertadecene and their derivatives present in Dalbergia sissoo trees play very vital role for keeping trees healthy. The Tukey HSD test, Scheffé, Bonferroni and Holm multiple comparison post-hoc tests clearly showed that Tetradecane and its derivative are significantly different in healthy and disease affected trees from each other.Bangladesh J. Bot. 51(3): 455-460, 2022 (September)